2019
DOI: 10.1038/s41594-018-0182-x
|View full text |Cite
|
Sign up to set email alerts
|

Nascent-protein ubiquitination is required for heat shock–induced gene downregulation in human cells

Abstract: hen eukaryotic cells are exposed to environmental stress, they mount an adaptive, conserved and coordinated response at the levels of transcription, translation, cell cycle and metabolism. The transcriptional response called the heat-shock response is typified by upregulation of heat-shock proteins or chaperones driven by the transcription factor heatshock factor (HSF) 1. Initially identified using heat-shock stress, the conserved HSF-driven response is now known to be induced by a variety of cellular conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 72 publications
2
65
0
Order By: Relevance
“…NELF has previously been shown to be dispensable for heat shock-induced gene upregulation in Drosophila cells (Ghosh et al, 2011), which is consistent with our findings. It has also been previously shown that gene downregulation upon heat shock is associated with pausing (Aprile- Garcia et al, 2019;Chen et al, 2017;Mahat et al, 2016a). We found that upon heat shock, RNA Pol II is paused at 1st pause regions for the downregulated genes, consistent with these studies.…”
Section: Function Of Nucleosome-associated Pausing In the Heat Shock Responsesupporting
confidence: 91%
“…NELF has previously been shown to be dispensable for heat shock-induced gene upregulation in Drosophila cells (Ghosh et al, 2011), which is consistent with our findings. It has also been previously shown that gene downregulation upon heat shock is associated with pausing (Aprile- Garcia et al, 2019;Chen et al, 2017;Mahat et al, 2016a). We found that upon heat shock, RNA Pol II is paused at 1st pause regions for the downregulated genes, consistent with these studies.…”
Section: Function Of Nucleosome-associated Pausing In the Heat Shock Responsesupporting
confidence: 91%
“…Aggregation in the nucleus could mean several different things. For example, during stress, proteins have been reported to enter the nucleoli (Frottin et al , 2019) and increase abundance at chromatin (Aprile‐Garcia et al , 2019). These could be linked to our results of increased thermal stability for soluble sub‐pools of aggregators that did not aggregate in heat shock (Fig 5B); the most strongly thermally stabilized proteins were indeed zinc‐finger containing DNA‐binding proteins (Fig 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation in the nucleus could mean several different things. For example, during stress, proteins have been reported to enter the nucleoli [61] and increase abundance at chromatin [62]. Although the nucleolus is actually proposed to act as a protein quality compartment [61], it is tempting to speculate that chromatin binding could also have protein quality aspects by stabilizing and sequestering unstable DNA-binding proteins during proteotoxic stress.…”
Section: Discussionmentioning
confidence: 99%